PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS LECTORA INSPIRE YANG DIINTEGRASIKAN DENGAN CAMTASIA STUDIO PADA MATA PELAJARAN GEOGRAFI MATERI SISTEM INFORMASI GEOGRAFI - Yemima Otoluwa; Sunarty Eraku; Daud Yusuf (JAMBURA GEO EDUCATION JOURNAL, 2020)
This research aims to develop Lectora Inspire based learning media on Geographic Information System material. Lectora Inspire is an application used to create learning media associated with Geographic Information System material which is integrated with Camtasia Studio. It applies a development research method with ADDIE model as an approach in compiling the learning media, Moreover, the validation are conducted by material expert, media expert, and subject expert. This learning media is tried out limited to high school student of grade XII trough questionnaire. The collected data is research finding regarding the quality of learning media and suggestions for product revisions. The validation result from material expert reveals that the value of media validation provided by validator I or material/content experts is 83.75% with valid category, validator II or product design expert is 88% with very valid category, while validator III or subject expert or teacher of geography subject is 98% with very valid category. Thus, the average of students respond towards the learning media is 88.8%.